Study on the time-frequency linkages between China’s economic policy uncertainty and the carbon emission trading market (Central China)—evidence from partial wavelet coherence analysis - Wu, Yaqi; Li, Zhenhao; Cheng, Yue; Yun, Po (Frontiers in Environmental Science, 2024)
In the context of carbon neutrality, the economic policy uncertainty (EPU) in various countries is constantly rising, and the carbon emission trading market (CET market) is constantly changing. This study uses the wavelet analysis to analyze the time-frequency linkages between China’s economic policy uncertainty index (CEPU) and the price-earnings ratios of the Hubei CET market (HCMP), a representative of Chinese CET markets, from short-run, medium-run, and long-run perspectives. Results show that from the perspective of correlation in the time domain, the HCMP is positively correlated with the CEPU in different time periods. From the perspective of causality in the frequency domain, there is a causal relationship between the HCMP and CEPU in the short run, and the CEPU fluctuations are ahead of the HCMP fluctuations in the medium run. In the long run, the HCMP fluctuations are ahead of those of CEPU for the period before 2021, but the two fluctuate synchronously for the period after 2021. This study provides a reference for policymakers to manage the CET markets and for investors to optimize their investment portfolios.